Preparation and characterisation of irradiated waste eggshells as oil adsorbent - Hasrin, N. I.; Othman, S. A. (2020)
Adsorption method had been developed by using natural organic adsorbent for the removal of oil because of its ability to bind the oil molecules into the surface of adsorbent. In this study, chicken eggshells waste was used and it undergoes irradiation process with four different amount of dose which was 0.5 kGy, 1.0 kGy, 1.5 kGy, and 2.0 kGy by using Gamma Cell Irradiator. Three equipment had been used for the characterization process which were the Scanning Electron Microscope (SEM), Energy Dispersive X-ray spectroscopy (EDX), and Fourier-Transform Infrared Spectroscopy (FTIR). The adsorption experiment was conducted to calculate the sorption efficiency by using different mass of samples. The result showed that irradiated chicken eggshells powder with 2.0 kGy amount of radiation dose has a best performance as oil adsorbent.